2017
DOI: 10.1007/s10461-017-1807-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Socio-demographic and Behavioral Determinants of HIV Testing and Counseling in HPTN 043/NIMH Project Accept

Abstract: Youth represent a large proportion of new HIV infections worldwide, yet their utilization of HIV testing and counseling (HTC) remains low. Using the post-intervention, cross-sectional, population-based household survey done in 2011 as part of HPTN 043/NIMH Project Accept, a cluster-randomized trial of community mobilization and mobile HTC in South Africa (Soweto and KwaZulu Natal), Zimbabwe, Tanzania and Thailand, we evaluated age-related differences among socio-demographic and behavioral determinants of HTC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…16,28 Consistent with previous studies, sociodemographic characteristics, including marital status, education, socioeconomic status, and employment, were strong predictors of HIV testing. 15,28,29 In our analysis, marital status was one of the strongest predictors for HIV testing, especially in Cambodia. The results demonstrated that married people were more likely to get tested for HIV.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…16,28 Consistent with previous studies, sociodemographic characteristics, including marital status, education, socioeconomic status, and employment, were strong predictors of HIV testing. 15,28,29 In our analysis, marital status was one of the strongest predictors for HIV testing, especially in Cambodia. The results demonstrated that married people were more likely to get tested for HIV.…”
Section: Discussionmentioning
confidence: 61%
“…9 The other two impactful predictors for getting tested for HIV were education and wealth status, which were also consistent with the findings from a previous study. 29 The women with higher education were more likely to get tested for HIV than those with low or no education. Similarly, the rich were more likely to get tested for HIV than the poor for wealth status.…”
Section: Discussionmentioning
confidence: 99%
“…Results also indicated that GDP per capita was associated with higher levels of PLHIV who know their status within a country. This result is unsurprising as studies across different settings and among various key populations have found a positive association between an individual's socioeconomic status and voluntary HIV testing . Surprisingly, health expenditure on HIV prevention efforts, that would typically include HIV testing education and awareness campaigns or interventions, was not statistically significant.…”
Section: Resultsmentioning
confidence: 95%
“…Despite major improvements in the availability of HTS in Eastern and Southern Africa, where the vast majority of HIV cases are found, an estimated 24% of people living with HIV were unaware of their status in 2017 [1]. Certain population subgroups remain persistently hard to reach, including young people (15–24 years) and males [2‐4]. Barriers to HTS have been documented (e.g.…”
Section: Introductionmentioning
confidence: 99%